2010
DOI: 10.1136/bjsm.2010.078725.225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yoga training on handgrip, respiratory pressures and pulmonary function

Abstract: Although there are a number of reports on the effect of yoga training on pulmonary functions, very few studies have been undertaken on the effect of yoga training on respiratory pressures and handgrip endurance. Hence the present work was planned to study the effect of yoga training on hand grip strength (HGS), hand grip endurance, forced expiratory volume (FEV), forced expiratory volume in 1 s (FEV 1 ) and peak expiratory fl ow rate (PEFR), 20 school children in the age group of 12-15 years were given yoga tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…[ 1 2 ] The positive health outcomes that have been observed include a decrease in blood pressure,[ 3 4 ] a decrease blood lipid values,[ 5 ] a decrease in body mass index,[ 4 ] as well as an improvement in pulmonary function. [ 6 7 ] From a performance standpoint, yoga has been reported to enhance muscle torque,[ 8 ] increase in handgrip strength,[ 9 ] decrease low back pain,[ 10 ] delay the onset of muscle soreness following strenuous activity,[ 11 ] increase flexibility and balance[ 12 ] as well as improved cardiovascular performance. [ 13 ] The impact of yoga has also been linked to improvements in mental health.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 2 ] The positive health outcomes that have been observed include a decrease in blood pressure,[ 3 4 ] a decrease blood lipid values,[ 5 ] a decrease in body mass index,[ 4 ] as well as an improvement in pulmonary function. [ 6 7 ] From a performance standpoint, yoga has been reported to enhance muscle torque,[ 8 ] increase in handgrip strength,[ 9 ] decrease low back pain,[ 10 ] delay the onset of muscle soreness following strenuous activity,[ 11 ] increase flexibility and balance[ 12 ] as well as improved cardiovascular performance. [ 13 ] The impact of yoga has also been linked to improvements in mental health.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Bronchial asthma patients also show a reduction in the number of attacks and use of medication as found by Bijlani RL in 2005. [3] Fulambark A et al [8] also found at Yoga has a positive effect on COPD patients.…”
Section: Discussionmentioning
confidence: 91%
“…Yoga training significantly improves lung functions and strength of inspiratory and expiratory muscles. ( 19 20 )…”
Section: Overweight and Obesitymentioning
confidence: 99%